THE HEART AND ITS POWER: A VIEW THROUGH THE LENS OF FOLK WISDOM - Vazira Ubaydullayeva (Modern American Journals, 2025)
This article, along with the valuable insights of great Uzbek medical scientists, examines the work of the heart – one of the body's organs that has acquired vital significance in human life.
Keywords: Right ventricle, left ventricle, Abu Ali ibn Sina, Korotkov method, phonendoscope, systolic blood pressure, diastolic blood pressure, pulse, wall arteries.